2004
DOI: 10.1111/j.1432-1033.2004.04150.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipids in Plasmodium falciparum

Abstract: Malaria remains a major health problem especially in tropical and subtropical regions of the world, and therefore developing new antimalarial drugs constitutes an urgent challenge. Lipid metabolism has been attracting a lot of attention as an application for malarial chemotherapeutic purposes in recent years. However, little is known about glycosphingolipid biosynthesis in Plasmodium falciparum. In this report we describe for the first time the presence of an active glucosylceramide synthase in the intraerythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Furthermore, previous studies have shown the involvement of transporter genes and membrane proteins that involved in the transport of drugs and lipids with antimalarial drug resistance [ 14 ]. Glycosphingolipids are important components of cellular membranes involved in various biological functions, and their biosynthesis was described in Plasmodium by an active malarial glucosylceramide synthase [ 91 , 92 ]. Marked lower levels of glycerophosphocholines in CQ-R compared to CQ-S and control groups and perturbation of the glycerophospholipid metabolism based on the pathway analysis indicates that there could be perturbed PLA2 activity in the CQ-R subjects before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown the involvement of transporter genes and membrane proteins that involved in the transport of drugs and lipids with antimalarial drug resistance [ 14 ]. Glycosphingolipids are important components of cellular membranes involved in various biological functions, and their biosynthesis was described in Plasmodium by an active malarial glucosylceramide synthase [ 91 , 92 ]. Marked lower levels of glycerophosphocholines in CQ-R compared to CQ-S and control groups and perturbation of the glycerophospholipid metabolism based on the pathway analysis indicates that there could be perturbed PLA2 activity in the CQ-R subjects before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…GM1 and GM3 are monosialic glycosphingolipids synthesized from glucosylceramide. The intraerythrocytic stage of P. falciparum includes an active glucosylceramide synthase that catalyzes the transfer of glucose to ceramide from UDP-glucose 48 . However, a previous report showed that P. falciparum did not biosynthesize or utilizes sialic acid 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipids constitute the major lipid class detected in parasite fractions removed from the erythrocyte, with phosphatidylcholine (PC) and phosphatidylethanolamine (PE) together accounting for ~50% of total lipid content [22,24,55,89]. These structural membrane components primarily contain two saturated or monosaturated FA chains [22], consistent with parasites requiring an exogenous supply of oleic and palmitic acid to sustain growth [21,23,24].…”
Section: Phospholipids In Plasmodiummentioning
confidence: 96%